Wirksamkeit von Arbeitsbeschaffungsmaßnahmen in Deutschland: empirische Befunde mikroökonometrischer Analysen - Reinhard Hujer; Stephan L. Thomsen (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– In a number of empirical studies, the effects of job creation schemes for participating individuals in Germany were analysed from various standpoints by means of microeconometric evaluation. Based on the findings of those studies, we assess the effectiveness of the programmes with regard to the aims stipulated by law. For this purpose the empirical results of the various studies are summarised and discussed critically. Two current studies are presented in particular detail that analyse the effects of job creation schemes using a data set which is so far unique as regards scope and information content. In the assessment it becomes clear that the studies are orientated towards the integration objective of job creation schemes. Moreover, it is clearly ascertainable that the evaluation of job creation schemes has to consider heterogeneity. For instance the measures are useful for some explicit target groups, whilst they reduce the labour market prospects of the majority of participants.
Keywords: 330; Arbeitsbeschaffungsmaßnahme - Erfolgskontrolle; Beschäftigungseffekte; berufliche Reintegration; arbeitsmarktpolitische Maßnahme